Analisis Sistem Distribusi Silase dan Respons Peternak terhadap Adopsi Pakan Fermentasi di CV. Irs Global Perkasa, Jawa Barat - unang yunasaf (Universitas Galuh, 2026)
This study aims to analyze the silage distribution system and farmers' responses to the adoption of fermented feed at CV. Irs Global Perkasa, West Java. A qualitative case study approach was used. Data were obtained through in-depth interviews, observation, and documentation, using a purposive sampling technique with farmers and the company. Data analysis was conducted using an interactive model and thematic analysis. The results indicate that the silage distribution system has implemented the POAC (Planning, Organizing, Actuating, Controlling) management function, but still has limitations in predictive planning and system integration. Good distribution quality influences farmer trust. Farmers' responses to silage were positive, indicated by its relative advantages, suitability, ease of trial and observation. However, obstacles remain, such as initial doubts and limited knowledge. This study concludes that the success of silage adoption is determined not only by product quality but also by the effectiveness of the distribution system and farmers' perceptions. Therefore, strengthening the technology-based distribution system and increasing education for farmers is necessary to encourage sustainable adoption.